PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK NIRVANA BEAUTY SUMBEREJO BALIKPAPAN - Ahmad Haerul Saleh; C. Prihandoyo; Nina Indriastuty (Fakultas Ekonomi Universitas Balikpapan, 2023)
The emergence of skincare provides a very new phenomenon in people's lives, especially young people, in particular they use skincare as a way to look physically perfect. Along with consumer needs for skin care, the production of the skincare cosmetics industry is also increasing, giving rise to cosmetic product marketing channels such as skincare factory outlets that provide skincare products that are not only used by women but also men. With this phenomenon, research is needed which aims to determine the effect of the marketing mix on purchasing decisions for Nirvana Beauty Sumberejo Balikpapan Products. The population used in this study was 1472 people during the last 3 months in 2022 and the sample used in this study was 305 respondents. The research method uses quantitative methods with the sample technique used, namely random sampling technique. Data collection was carried out by means of observation, interviews, and distributing questionnaires. The test equipment used in this study is multiple linear regression analysis, classical assumption test and partial hypothesis testing (t-test). The results of the analysis in partial testing of the product, promotion, and place variables have a positive and significant effect on product purchasing decisions, while the price variable has a negative and insignificant influence on purchasing decisions for Nirvana Beauty Sumberejo Balikpapan products. The variable that has the most dominant influence on purchasing decisions is the promotion variable.